The Impact of Green Accounting on Firm Value in the Basic Materials Sector - Dita Yuninalita Dian Parastuti; Dewi Ayu Puspita; Indah Purnamawati (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
Industrial activities in the basic material sector have caused significant environmental damage, thereby driving the implementation of green accounting concepts to reduce negative environmental impacts while enhancing corporate value. This research seeks to analyze study delves into how expenditures dedicated to environmental initiatives, the effectiveness of a company’s sustainability practices, and the extent of its ecological transparency contribute to shaping its overall market valuation within the sector examined in operating as listed entities on the Indonesian capital market during the 2021-2023 period. This investigation adopts a quantitative methodology by utilizing multiple linear regression techniques to examine the relationships among the variables under study on secondary data sourced from the annual and sustainability reports of companies. The research sample includes 89 companies selected based on specific criteria. Data analysis reveals the findings reveal that expenditures on environmental activities, along with sustainability performance, contribute positively to a firm’s value, while the degree of environmental reporting appears to have no notable effect. The study results confirm that corporate investment in environmental management can enhance legitimacy before stakeholders, which strengthens institutional theory. However, transparency in environmental information disclosure has not yet become a primary consideration in investment decisions, thus it does not impact corporate value. Theoretically, this study strengthens the institutional theory by proving the role of environmental investment in creating legitimacy and value creation. Practically, this study provides current perspectives for both companies and investors on the significance of environmental investment compared to mere disclosure in enhancing corporate value.